2023
DOI: 10.1177/03946320231154988
|View full text |Cite
|
Sign up to set email alerts
|

High serum leptin and adiponectin levels as biomarkers of disease progression in Egyptian patients with active systemic lupus erythematosus

Abstract: Objectives: Leptin and adiponectin are adipose-derived immune modulators (adipokines) that may contribute to SLE pathology and symptoms. This study aimed to evaluate the associations of serum adiponectin and leptin with clinical manifestations and disease activity in SLE patients. Methods: This is a case control study, where 70 SLE patients and 50 age- and sex-matched healthy controls were enrolled from the Rheumatology and Rehabilitation Department of Beni-Suef University Hospital from June 2020 till April 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 39 publications
0
2
0
1
Order By: Relevance
“…Although the activation of ALB was reported to be associated with disease progression, the ALB is decreased during the active stage of LN [29]. ALB was found to not be independently inversely associated with the presence and severity of LN, as evidenced by increased adiponectin and serum leptin [30]. Data from a study of 182 LN patients who underwent prebiopsy blood tests demonstrated that serum albumin showed a signi cantly decreased serum albumin (P = 0.048) and lower platelet count (P = 0.03) compared to the non-LN group [28].…”
Section: Discussionmentioning
confidence: 81%
“…Although the activation of ALB was reported to be associated with disease progression, the ALB is decreased during the active stage of LN [29]. ALB was found to not be independently inversely associated with the presence and severity of LN, as evidenced by increased adiponectin and serum leptin [30]. Data from a study of 182 LN patients who underwent prebiopsy blood tests demonstrated that serum albumin showed a signi cantly decreased serum albumin (P = 0.048) and lower platelet count (P = 0.03) compared to the non-LN group [28].…”
Section: Discussionmentioning
confidence: 81%
“…Since the elevation of proinflammatory cytokines is a common mechanism of SLE activity and obesity, MetS may be an important factor bridging chronic systemic inflammation and accelerated atherosclerosis in SLE. The role of adipokines, such as leptin and adiponectin, in SLE remains unclear, though high serum leptin and adiponectin levels are biomarkers of disease progression in SLE [ 36 ]. Another significant Harmonizome term was ‘asthma’.…”
Section: Resultsmentioning
confidence: 99%
“…Ці адипокіни можуть мати вплив на метаболізм, запалення, патологічні зміни, пов'язані з ожирінням, метаболічним синдромом, серцево-судинними захворюваннями, а також беруть участь у запальних, аутоімунних та ревматологічних захворюваннях, серед яких ревматоїдний артрит [10], хвороба Бехчета та СЧВ. [8][9][10][11][12][13].…”
Section: вступunclassified